The role of anatomical and functional orientation in identification of parathyroid glands for patients with parathyroidectomy - Zhou, Peng; Xu, Jing; Guo, Yinghao; Chen, Lanqing; Liu, Yongxiang; Guo, Haonan; Shao, Changxiu; He, Qingqing (Frontiers in Endocrinology, 2024)
Objective: To investigate diagnostic approaches for preoperative localization of secondary hyperparathyroidism, as well as to give surgeons with precise parathyroid gland localization and imaging so that surgery can be performed safely. Methods: The clinical data of 710 patients with secondary hyperparathyroidism who underwent surgery in our center from October 2009 to October 2023 were retrospectively analyzed.The changes in calcium, phosphorus, and parathyroid hormone levels were observed to ascertain the anatomical location and number of parathyroid glands. Results: Among the 710 patients, 55 underwent total parathyroidectomy, the others underwent total parathyroidectomy with autotransplantation. In total, 2,658 parathyroid glands were removed, with 43 glands being removed in 35 reoperation cases. The median parathyroid hormone level at 6 months postoperatively was 13.40 (interquartile range, 7.00-29.80) pg/mL. The detection rates of the parathyroid glands before first and repeat surgeries were higher using 99m Tc-MIBI SPECT/CT fusion imaging than ultrasound (P ＜ 0.05). The sensitivity of combined preoperative 99m Tc-MIBI SPECT/CT and ultrasound was 92.31%, higher than that of either 99m Tc-MIBI SPECT/CT fusion imaging or ultrasound alone (P < 0.05). The incidence of ectopic parathyroid glands was 23.8%, and the incidence of ectopic left lower parathyroid glands was 13.2%. The left lower parathyroid gland was the most prone to ectopia. Conclusion: 99m Tc-MIBI SPECT/CT fusion imaging, paired with high-frequency ultrasound, can be utilized to diagnose SHPT preoperatively. The most common ectopia site is the left lower parathyroid gland, which is located primarily in the thymus and superior mediastinum.Understanding the functional anatomical distribution of the parathyroid glands is critical for developing effective surgical methods for secondary hyperparathyroidism.